2015
DOI: 10.1002/2014jd022927
|View full text |Cite
|
Sign up to set email alerts
|

Convective intensity, vertical precipitation structures, and microphysics of two contrasting convective regimes during the 2008 TiMREX

Abstract: This study investigates the convective/microphysical properties and precipitation structures of seven rainfall events in southwest Taiwan during the 2008 Terrain-influenced Monsoon Rainfall Experiment (TiMREX). TiMREX heavy rainfall events (>50 mm d À1 ) are characterized by upstream low-level jets, unstable upstream conditions, and a nearly moist neutral stratification within the heavy rain region. Three heavy rainfall events (2, 5, and 16 June) have only weak to moderate convection and little lightning; e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
1
3
0
1
Order By: Relevance
“…This event occurred around coastal regions, where continental and maritime influences coexist (Lang et al., 2010). Consistent with previous studies focusing on convections at subtropical regions (e.g., Chang et al., 2015; Rowe et al., 2011, 2012; Xu & Zipser, 2015), results in this study show that different meteorological forcings can lead to the variability in the microphysical structure of different types of convections. Moreover, the low‐level rotation might be an important factor leading to more large raindrops.…”
Section: Discussionsupporting
confidence: 92%
“…This event occurred around coastal regions, where continental and maritime influences coexist (Lang et al., 2010). Consistent with previous studies focusing on convections at subtropical regions (e.g., Chang et al., 2015; Rowe et al., 2011, 2012; Xu & Zipser, 2015), results in this study show that different meteorological forcings can lead to the variability in the microphysical structure of different types of convections. Moreover, the low‐level rotation might be an important factor leading to more large raindrops.…”
Section: Discussionsupporting
confidence: 92%
“…Although storms appear larger in IMERG, MRMS represents the storms as having higher peak intensities (Fig. 4e), which may be caused by the aggregation of rain particles within the storms' cores at lower altitudes leading to the formation of heavier droplets, falling faster, compared to the precipitation at high levels within the cloud (Xu and Zipser 2015). In addition, the higher spatiotemporal resolution of MRMS compared to IMERG also contributes to a better representation of the heavy precipitation rate in the storm cores.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Zhang et al (2017) noticed a distinct RSD in different squall-line stages and different precipitation types. In Southern Taiwan, Xu and Zipser (2015) concluded that heavy rainfall is mostly associated with a quasi-stationary mei-yu front and that upstream low-level jets and unstable upstream conditions constrained with moist neutral storm environments trigger heavy precipitation. Besides, storm initiation and evolution (Xu et al 2012), as well as kinematic structures and microphysical characteristics (Chang et al 2015;Jung et al 2012), were observed by a Doppler radar.…”
Section: Introductionmentioning
confidence: 99%